2007
DOI: 10.1103/physrevd.75.023516
|View full text |Cite
|
Sign up to set email alerts
|

Noninflationary model with scale invariant cosmological perturbations

Abstract: We show that a contracting universe which bounces due to quantum cosmological effects and connects to the hot big-bang expansion phase, can produce an almost scale invariant spectrum of perturbations provided the perturbations are produced during an almost matter dominated era in the contraction phase. This is achieved using Bohmian solutions of the canonical Wheeler-de Witt equation, thus treating both the background and the perturbations in a fully quantum manner. We find a very slightly blue spectrum (n S −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 42 publications
5
117
0
9
Order By: Relevance
“…This is also consistent with predictions from loop quantum gravity [83,84], where it is shown that the era of accelerated expansion will be followed by an era of contraction. It may be noted that unstable geometries can mathematically decay into bubble of nothing, which contain neither matter nor spacetime [85,86].…”
Section: Deformed Wheeler-dewitt Equationsupporting
confidence: 79%
“…This is also consistent with predictions from loop quantum gravity [83,84], where it is shown that the era of accelerated expansion will be followed by an era of contraction. It may be noted that unstable geometries can mathematically decay into bubble of nothing, which contain neither matter nor spacetime [85,86].…”
Section: Deformed Wheeler-dewitt Equationsupporting
confidence: 79%
“…On the other hand, the behavior of quantum fluctuations during this period and their link with the emerging primordial matter power spectrum are complicated issues which deserve more profound investigation. See also [28][29][30].…”
Section: Integration Of the Exactly Solvable Casesmentioning
confidence: 99%
“…In this case, the issue of the wavefunction collapse becomes irrelevant since it just corresponds to a situation where the observer updates its knowledge (in the Bayesian sense) about the physical properties of the system. Other attempts, such as the non-local hidden variable theories, have also been tried [52][53][54][55][56][57]. In all these cases, the cosmological situation does not differ much from a conventional laboratory situation and, moreover, does not lead to new, falsifiable, predictions 1 .…”
Section: Introductionmentioning
confidence: 99%